Postoperative Complications in Obstructive Sleep Apnea Patients: A Comparison between Single and Multilevel Surgery. (2nd September 2014) - Chan, Ching Yee; Han, Hong Juan; Toh, Song Tar
Abstract : Objectives: Evaluate the difference in the postoperative complication rate between single and multilevel surgery performed on patients with obstructive sleep apnea (OSA). Methods: A retrospective outcomes analysis was performed on 238 patients with OSA who underwent surgery from January 2011 to December 2013 under the care of the third author in a tertiary referral center. Complications were defined as unexpected events needing additional medical attention within 30 days of surgery. These included but were not limited to: emergency department visits, nasal packing, cautery in the outpatient setting, hospitalization, and need for return to the operating room. Early complications were those occurring within the first 24 hours of surgery while late complications were defined as those occurring after 24 hours. Results: Of 238 patients, 88 underwent single level surgery and 150 underwent multilevel surgery. There were none lost to follow‐up. The main complication was bleeding. The complication rate was 5.7% in the single level group and 14.7% in the multilevel group. The difference in complication rate was significant, with P <. 05. The confidence interval was from 1.04 to 7.83 and the odds ratio was 2.85. Conclusions: There is an overall higher complication rate in obstructive sleep apnea patients undergoing multilevel surgery. However, the overall risk remains low and most complications are minor. This reminds us to be cautious in the management of such patients, especially if they have had multiple procedures performed.